KETERKAITAN PERTUMBUHAN PENJUALAN PERPUTARAN PERSEDIAAN, PERPUTARAN PIUTANG, DAN PERPUTARAN KAS TERHADAP PROFITABILITAS PERUSAHAAN LQ 45 DI BURSA EFEK INDONESIA - Sugiyarmasto Sugiyarmasto; Erlina Setyaningrum (ITB AAS INDONESIA Surakarta, 2021)
The research aims to determine and provide empirical evidence of , sales growth inventory turnover, receivables Turnover, and significant cash turnover on profitability in LQ 45 Company on Indonesia Stock Exchange year 2016-2018. The samples in this study used purposive sampling so obtained 21 company samples from 45 LQ 45 company population listed on the Indonesia Stock Exchange, with 63 observations of financial statements (21 companies x 3 years of financial statements warning). Dependent variables in this study, namely profitability. While independent variables in this study, sales growth namely inventory turnover, turnover receivables, , cash turnover. The data analysis method used is a type of multiple regression test to test the relationship of independent variables with the dependents The results of the research hypothesis testing proved that the turnover of receivables, and cash turnover significantly positively affect profitability. And sales growth has a negative and significant effect on profitability. While inventory turnover has a negative and insignificant effect on profitability in LQ 45 company in the Indonesia Keywords: sales growth,inventory turnover, turnover receivable, cash turnover,profitability